Factors Impacting on Undergraduate Students’ Continuance Intention to Use Shiyibao Intelligent Translation Practice and Teaching Platform: A Case Study of a Private University in Guangdong, China - Yan, Fang (Scholar: Human Sciences, 2025)
Purpose: This research aims to explore the factors influencing the continuance intention of undergraduate students to use the Shiyibao Intelligent Translation Practice and Teaching Platform in a private university in Guangdong, China. There are five independent variables, namely perceived usefulness, satisfaction, learning engagement, performance expectation and attitude, and one dependent variable, continuance intention. Research design, data, and methodology: The research employed the Index of Item-Objective Congruence (IOC) for validity and a Cronbach’s Alpha in a pilot test (n=30) for reliability. 80 valid responses from students of English-related majors (English majors, Business English majors, and Translation majors) at Zhanjiang University of Science and Technology were analyzed by multiple linear regression to verify the significant relationship between variables. Following this, a group of 30 students underwent an 8-week IDI. Afterward, the quantitative results from post-IDI and pre-IDI were analyzed in the paired-sample t-test for comparison. In addition, eight students were also interviewed at both pre-IDI (for designing intervention) and post-IDI (for affirming the effectiveness of the intervention) stages. Results: In multiple linear regression, the study revealed that perceived usefulness, satisfaction, learning engagement, performance expectation, and attitude significantly impacted students’ continuance intention to use Shiyibao. Conclusion: The results from the paired-sample t-test for comparison demonstrated significant differences in all the variables between the post-IDI and pre-IDI stages.